A Smile Reimagined: Gummy Smile Resolution with Cutting Edge Method Using Chu’s Gauge and Polymethylmethacrylate (PMMA) Bone Cement - Shalini Mundra; Neetha. J. Shetty (Case Reports in Dentistry)
Excessive gingival display (EGD) is one of the most common aesthetic concerns, and its correction often presents a challenge to periodontists. It has a multifactorial etiology, and this article describes a case involving hypermobile upper lip (HUL), altered passive eruption (APE), and vertical maxillary excess (VME). Upon investigation, a positive collum angle and marked subnasal skeletal depression were observed. In this context, it is noted that during a spontaneous smile, the upper lip retracts and gets lodged in this depression. The rehabilitation plan includes included aesthetic crown lengthening via gingivectomy using Chu’s proportional gauge for altered passive eruption and filling the subnasal depression by PMMA (polymethylmethacrylate) bone cement. The entire treatment plan was digitalised using cutting edge methods such as computed tomography (CT), cone beam computed tomography (CBCT), and 3D printers for virtual planning of the defect’s position, size, and shape. No postoperative complications were reported. After six months, the patient exhibited a harmonious smile with reduced exposed gingiva.